Ex-Situ Actors and Their Contribution to Conservation-Development Agenda in Old Oyo National Park (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Effects of a green globe is felt even far away from the point of greening. Biodiversity protection or otherwise has far reaching effects even beyond the source zone. This has fueled the need for this research, gauging contribution of external actors on park protection in Old Oyo National Park (OONP). Two sets of questionnaire were administered to park officers and Support Zone Communities (SZCs) assisted with organized Focused Group Discussions (FGDs) in each of the six ranges of the park. Secondary data augments survey from records obtained from the park head office at Isokun. A total of 70 PMs were surveyed purposively at the Park headquarters and at the six ranges. From a sampling frame of 30%, a total of 40 villages were randomly and unevenly pooled from all six range stations depending on number of villages per range. Five households were randomly selected each and the household heads were purposively sampled. This was aided with FGD sessions. Most (74%) of the SZCs engage in farming, some (22.5%) practice both hunting and herding with overlap in each case. Average annual PCI for the SZCs was lesser than that of the PMs. External actors engage with the SZCs in economic empowerment, park-community synergy and more. These activities were agreed by PMs (42.86%) to be in concord with sustainable conservation, while SZCs agreed that park-community collaboration benefit them (66.5%). Community empowerment and partnership among others are inevitable to attain social acceptability, economic viability and ecological sustainability of park resources.